درجة استخدام أ عضاء هيئة التدريس بكلية التربية جامعة اب ل ساليب التقويم المس تمر والتغذية الراجعة من وجهة نظر طلابهم - مرشد القواس, محمد أحمد (Université de M'sila, 2016)
هدفت الدراسة الحالية التعرف على درجة اس تخدام أعضاء هيئة التدريس بكلية التربية جامعة اب لساليب التقويم المس تمر، والتغذية الراجعة من وجهة نظر طلابهم، والكشف عن الاختلاف بين وجهة نظر الطلبة في اس تخدام أساتذتهم أساليب التقويم المس تمر، والتغذية الراجعة باختلاف التخصص، والمس توى الدراسي، والجنس، وتكونت عينة الدراسة من 258 طالباً وطالبة من كلية التربية جامعة اب، وتوصلت الدراسة الحالية لعدد من النتائج أهمها: ان درجة اس تخدام أعضاء هيئة التدريس بكلية التربية جامعة اب لساليب التقويم المس تمر، والتغذية الراجعة كانت بدرجة ضعيفة، تختلف وجهة نظر الطلبة في درجة اس تخدام أعضاء هيئة التدريس بكلية التربية جامعة اب أساليب التقويم المس تمر، والتغذية الراجعة تعزى لمتغير التخصص) انساني، علمي، تربوي( لصالح التخصص التربوي، بينما لا تختلف وجهة نظر الطلبة في درجة اس تخدام أعضاء هيئة التدريس بكلية التربية جامعة اب أساليب التقويم المس تمر والتغذية الراجعة تعزى لمتغير المس توى الدراسي، ومتغير الجنس، و أوصي الباحث بعدد من التوصيات منها: اعداد الدورات التدريبية أثناء الخدمة لعضاء هيئة التدريس بجميع الكليات من أجل تزويدهم بالكفايات والمهارات المهنية أثناء قيامهم بعملية التدريس، وتزويدهم بالمهارات التي تمكنهم من اختيار واس تخدام أساليب التقويم المس تمر، والتغذية الراجعة. -Abstract: The present study aimed at knowing what a range the teaching staff in the Faculty of Education – Ibb University, use the methods of continuous evaluation and feedback from their students ' point of view, and finding out the differences between the perspective of the students toward their teachers' use of the different methods of continuous assessment and feedback according to the different specializations, academic levels and gender. For the study sample consisted of 258 students from the College of Education- Ibb University. the current study findings were: That the use of the teaching staff -Faculty of Education/ Ibb University of the methods of continuous assessment and feedback was too weak, and the students' perspective in the of use of f those methods varies according to the variable specializations methods (Human, scientific, educational) for the educational specialization، while the viewpoint of the students for what a range of use of the teaching staff/ Faculty of Education/ Ibb University of the continuous assessment methods and feedback due to the variable of the study level and the variable of sex do not differ. the Researcher has recommended some devices and directions, which are as the follows: the preparation of in-service training course for the teaching staff in all the different faculties to provide them with the skills and the qualifications that enable them to choose and use the methods of continuous evaluation and feedback.
Keywords: ااستخدام اساليب التقويم